O SIGNIFICADO DA GESTÃO PARA OS COORDENADORES DE CURSO SUPERIOR - Tainá Rodrigues Gomide Souza Pinto (Universidade Federal de Santa Catarina, 2019)
The purpose of this study is to understand the meanings of management held by the coordinators of higher education of a federal university of Minas Gerais. It is based on the teachings of Henry Mintzberg (2010). For data collection, semi-structured interviews were carried out, and the results were systematized with the help of content analysis techniques. It was verified that the coordinators understand the management of the advanced course as the act of managing their pedagogical project; as the existing articulation between the students and the superior administration of the university and as the bureaucratic and organization process that embeds the course. Among the observed characteristics, what stands out is an accelerated rhythm, in which varied activities are developed in a fragmented way. Coordinators face challenges in dealing with the lack of material and human resources and the lack of a job training policy. Also the challenge of conciliating the managerial activies with the other activities of the teaching career, with no incentive policy in sight. The article concludes that although the coordinator is managing the training of future professionals, she is left alone in a bureaucratic and political structure, in which she reacts to actions but doesn’t act strategically.